Energy and protein requirements of commercial broilers in winter - NAGRA, S S; CHAWLA, J S (The Indian Journal of Animal Sciences, 2013)
Energy and protein requirements of commercial (IBL-80) broilers were determined under the cold climatic conditions In a 3 x 3 factorial design using 20, 22 and 24% protein levels, each with 2 500, 2 700 and 2900 Kcal metabolizable energy (ME) per kg diet, A single diet feeding programme was followed from day-old to 56 days of age. Protein content of the diet had significant (P<0.05) effect on growth rate, but it mfluenced the efficiency of feed utilization during first 42 days of age only. Energy content of the diet had significant (P<0,05) effect on growth me and efficiency of feed utilization both at 42 and 56 days of age, The shank and keel length, breast angle, abdominal fat deposition and evisceration percentage increased with the increase in energy Content of diet. The highest interaction effect of protein x energy combination was reflected in 22Â·24% protein on growth rate and 20-22% protein on efficiency of feed utilization with 2900 Kcal ME/kg diet. The least amount of protein per unit gain in live weight was required in 20/2 900 combination but the energy cost was mioimum in 22/2 900 combination. The cost on feed per unit weight gain was minimum in 20/2 900 combination. Considering all economical parameters, a level of 20% protein with 2 900 Kcal ME/kg diet was recommended in a single diet feeding programme for optimum performance of commercial broilers during the cold climatic conditions, Rearing of birds beyond 42 days of age involved higher feeding cost per unit weight gain due to lowered efficiency of feed utilization,